Training, supervision and therapists' adherence to manual-based therapy - Cox, D; Burgess, M; Chalder, T; Sharpe, M; White, P; Clark, L (2013)
Objectives: To describe the development, delivery and quality control of three manual-based therapies as given in an inter-professional multi-centre randomized controlled trial of therapies for chronic fatigue syndrome (CFS). Methods: Experienced therapy leaders were recruited. These therapy leaders then developed the treatments and therapy manuals, piloted them, and planned training and supervision. Appropriately-qualified therapists were recruited to deliver each therapy and trained in the specific therapy philosophy, model and delivery. Training and supervision was face-to-face and by telephone, and included reviewing audio recordings of therapy sessions. Results: At the end of the trial, the therapists delivering all three trial therapies were similarly highly rated as adhering well to their manuals and scored similarly and highly on therapeutic alliance with patients and therapy differentiation. Conclusions: High-quality delivery of therapy can be achieved if there is an experienced therapy lead, if therapy manuals have been piloted, and if therapists are well trained and supervised, including the review of recorded treatment sessions. Routine clinical practice could benefit from the implementation of these procedures.